On a resonant elliptic problem with singular terms. (June 2020) - Anello, Giovanni; Faraci, Francesca
Abstract: In the present paper we consider the singular resonant elliptic problem ( P μ ) − Δ u = λ 1 u + ( u s − 1 − μ u r − 1 ) χ u > 0 , in Ω u ≥ 0 in Ω u = 0, on ∂ Ω and prove the existence of a non trivial solution in the cases 0 < r < s < 1 and 0 < s < r < 1 .